NEW OPPORTUNITIES PHARMACOTHERAPY PATIENTS WITH REFRACTORY EPILEPSY - P. N. Vlasov (Эпилепсия и пароксизмальные состояния)
Objective: to generalize the Russian experience with perampanel (PER) in routine clinical practice; to do this, the results of its use as an adjuvant partial epilepsy medication were retrospectively assessed. The study is still in progress now; therefore, the paper gives its preliminary results.Materials and methods. The investigation included 52 patients with drug-resistant partial epilepsy. Their mean age was 28.92±14.02 years (a small number of the patients had not attained the age of 12 years); the proportion of men was 56%; the disease duration was over 10 years (69.2%); symptomatic epilepsy was in 76.9% with an epileptic focus being in the frontal (46.2%) and temporal (44.2%) regions. PER was prescribed to the majority (71.2%) of patients after three previous therapy lines. The baseline monthly rates of all types of seizures were 127.29±82.29; those of generalized seizures were 6.72±1.90.Results. After addition of PER to therapy just within the first month, there was a significant reduction in the frequency of all types of seizures to 52.06±29.26 per month (Sign test; p=0.00001) and in that of secondary generalized seizures to 3.71±1.71 (Sign test; p=0.00001). The duration of PER administration was more than 6 months in the overwhelming majority of cases. In 58% of the patients, the frequency of seizures decreased by more than 50% (respondents). The lack of all types of seizures was noted in 8%; that of only secondary generalized seizures was in 31%. Adverse events were observed in 30.1% of the patients (aggression in 11.5% and somnolence in 9.6%; others were seen more rarely). The dose of PER was decreased because of side effects in 7 (13.5%) patients; the drug was discontinued in 4 (7.7%). The mean dose of PER for adults was as high as 6 mg.